Re‐evaluation of sodium, potassium and calcium salts of fatty acids (E 470a) and magnesium salts of fatty acids (E 470b) as food additives. (2nd March 2018) - ,; Younes, Maged; Aggett, Peter; Aguilar, Fernando; Crebelli, Riccardo; Dusemund, Birgit; Filipič, Metka; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Kuhnle, Gunter Georg; et al.
Abstract: The EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) provides a scientific opinion re‐evaluating the safety of sodium, potassium and calcium salts of fatty acids (E 470a) and magnesium salts of fatty acids (E 470b) when used as food additives. In 1991, the Scientific Committee on Food (SCF) established a group acceptable daily intake (ADI) 'not specified' for the fatty acids (myristic‐, stearic‐, palmitic‐ and oleic acid) and their salts. The sodium, potassium, calcium and magnesium salts of fatty acids are expected to dissociate in the gastrointestinal tract to fatty acid carboxylates and their corresponding cations. There were no data on subchronic toxicity, chronic toxicity, reproductive and developmental toxicity of the salts of fatty acids. There was no concern for mutagenicity of calcium caprylate, potassium oleate and magnesium stearate. From a carcinogenicity study with sodium oleate, a no observed adverse effect level (NOAEL) could not be identified but the substance was considered not to present a carcinogenic potential. Palmitic‐ and stearic acid which are the main fatty acids in E 470a and E 470b were already considered of no safety concern in the re‐evaluation of the food additive E 570. The fatty acid moieties of E 470a and E 470b contributed maximally for 5% to the overall intake of saturated fatty acids from all dietary sources. Overall, the Panel concluded that there was no need for a numerical ADI and that the food additives sodium, potassium, calcium and magnesium salts of fatty acids (E 470a and E 470b) were of no safety concern at the reported uses and use levels.